Colonial Building Typology in Surabaya Old City Area Case Study: Rajawali Street Corridor - Aditiya; Wikatiyoso, Respati; Suhartono, Tonny (Proceedings of International Conference of Graduate School on Sustainability, 2025)
This study examines the architectural typology of colonial buildings in the Jalan Rajawali corridor in Surabaya, emphasizing the importance of preserving historical structures amidst modernization. The purpose of this study is to document and analyze the characteristics of these buildings, which are crucial in maintaining the city’s cultural heritage. Preserving colonial architecture is not only important for historical continuity, but also crucial in strengthening Surabaya’s distinctive identity as a city with a rich colonial heritage. The results of this study highlight the importance of Rajawali Street, formerly known as Heerenstraat, as a center that displays many Dutch colonial buildings. This building typology reflects the historical footprint of the Dutch in Indonesia and their role in regional trade during the colonial period. This study categorizes colonial buildings based on their facades, layouts, and materials, revealing a diverse range of architectural styles that reflect both aesthetic and historical values. In terms of methodology, this study uses comparative analysis to identify architectural similarities and differences between buildings. This approach is based on the principles of architectural typology, which studies the basic characteristics of architectural objects. This study also discusses specific examples, such as the Internatio Building and the Cerutu Building, which demonstrate distinct colonial architectural features, including massive forms, symmetrical layouts, and adaptation to tropical climates. In conclusion, this study emphasizes the importance of protecting these colonial buildings as part of Surabaya’s historical landscape. The findings contribute to the broader discourse on heritage conservation by advocating for policies that recognize and preserve colonial-era architectural heritage in urban environments.